Incidencia de redes sociales en el tiempo libre de los adolescentes de 12 a 15 años del Barrio Esperanza, Cantón Olmedo, año 2024 - Vargas Ordoñez, Katty Elizabeth (2025)
The present work shows the influence that social networks have on the lives of adolescents aged 12 to 15 years, as it develops in the Esperanza neighborhood of Olmedo canton, addressing the year 2024. The general objectives were to establish how to experience the use of social networks, identify their causes, effects and formulate a proposal for action in order to optimize their use. This was qualitative research with an inductive perspective, applying the technique of cross-sectional focus groups with a group of 20 adolescents in order to capture their perceptions and experiences in relation to the subject matter. The results found show that the use of social networks has become a dominant activity for young people thanks to their access to electronic devices; the main causes of misuse among adolescents can be summarized as the absence of limits on use by parents, the need for social validation on their part and loneliness. These aggravating factors lead adolescents to use social networks as a means of escape, which in turn has a negative impact on their well-being, manifesting itself in anxiety, sadness and poor performance at school, affecting their quality of life and family relationships. The article also reports the disconnection of interests and concerns of adolescents and the lack of knowledge on the part of their parents about their children's interests and problems. The study details that 70% of adolescents consider the main cause of excessive use of social networks to be the lack of parental intervention, which implies poor school performance and less family interaction. The search for social validation stands out as an important element in the use of social networks. The research concludes with the confirmation of the need to influence the responsible use of social networks by adolescents, establishing specific limits and promoting communication within the family. Educational activities that address the safe and healthy use of social networking platforms are proposed